RELATIONSHIP OF VOCABULARYMASTERY WITH HIGH SCHOOL STUDENTS’ SPEECH TEXT WRITING SKILLS SOURCED FROM LITERARY WORKS - Wiskarnid, Wiskarnid; Tatalia, Ricci Gemarni; Rahmat, Wahyudi (Magistra Andalusia: Jurnal Ilmu Sastra, 2022)
This study aims first to describe the vocabulary mastery of class XI students of SMA N 4 West Sumatra. Second, define the writing skills of class XI students of SMA N 4 West Sumatra. Third, describe the relationship between vocabulary mastery and writing skills of class XI students of SMA N 4 West Sumatra.This type of quantitative research with correlation method. The research population is class XI students of SMA N 4 West Sumatra in 2021/2022. The sample in the study of students of class XI IPS 2 amounted to 34 people. This research data is the score of the objective test of vocabulary mastery and the score of writing lecture texts for class XI SMA 4 West Sumatra students. Based on the results of the study concluded as follows. First, the vocabulary mastery of class XI students of SMA N 4 West Sumatra obtained an average score of 71.38 in the range of 66-75% on a scale of 10, with qualifications more than adequate (LdC). Second, the writing skills of class XI students of SMA N 4 West Sumatra obtained an average score of 78.33 in the range of 76-85% on a scale of 10, with a qualification of Good (B). Third, there is a significant relationship between vocabulary mastery and writing skills of class XI students of SMA N 4 West Sumatra. Then the hypothesis is accepted because the test results prove that tcount> from ttable is 2.39> 1.70. This proves that vocabulary mastery is related to students' text writing skills.